Elena Aitzkoa : paisaje de amor. Materia, escala y tema Elena Aitzkoa - Mendizabal, Elena, 1960- (2017)
This text addresses the sculptural work of Elena Aitzkoa Reinoso (Vitoria-Gasteiz 1984). She is a multidisciplinary artist who performs, writes and makes sculptures. He makes his sculptures transforming materials and three-dimensional objects having a strong role the color. Through her writings and the structure of her works we appreciate the importance that the artist has for the affection, nature and the experience of her own body. The article deals with works from aspects such as: matter, scale, nature and the installation of works